Elaboración e implementación de un plan de negocios en la empresa riotronics de la ciudad de Riobamba y su incidencia en el posicionamiento de la misma. Período enero – junio 2014. - Vásconez Vásconez, Henry David (2015)
The present research was aimed at developing and implementing a business plan for the company Riotronics of Riobamba and its impact on the positioning of it, for the period JanuarytoJune2014.The effect were develop all phases of that plan, starting with the executive summary, then the unit runs, following market researcher business plan, operational plan, financial structure (investment and financing) and the financial plan. Within the executive unit basic data of the company, market study determined the unmet demand for computers in the business plan could verify the usefulness presenting the income statement projected in each of the years presented projection plan. Subsequently, the economic and financial evaluation was conducted to determine the feasibility and practicality of implementation. The financial evaluation required to determine feasibility several indicators such as Net Present Value, Internal Rate of Financial Return, Benefit Cost Ratio, the period of Pay back and Break Even as a management tool was calculated. Finally the results of market research and market study, it was conducted in the same field of the facts presented. With the development and implementation of the business plan and all stages developed technical and methodological way, it can be concluded that the company y improve its position in the market for computers. All these records leads to the conclusion that based on the analysis of the results and evaluation indicators set can be shown to the general hypo thesis is accepted. It is therefore recommended that the implemented business plan can be applied in the company and can be replicated in other similar companies, to help improve your management and business management, with the achievement of favorable technical and economic results.